Testyfing to the truth : Eyewittnesses to the Holocaust - Wiener Library (2021)
"During the 1950s researchers at The Wiener Holocaust Library gathered over 1,000 accounts from eyewitnesses to Nazi persecution and genocide." [self-decription]